2014
DOI: 10.2217/epi.14.79
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Nasopharyngeal Carcinoma Methylome Identifies Aberrant Disruption of Key Signaling Pathways and Methylated Tumor Suppressor Genes

Abstract: The NPC methylome shows a special high-degree CpG methylation epigenotype, similar to the Epstein-Barr virus-infected gastric cancer, indicating a critical epigenetic etiology for NPC pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 86 publications
3
46
0
Order By: Relevance
“…First, we examined the effects of SFRP1 on NPC cells using MTT, colony formation, wound-healing, and Transwell assays, which showed that cell proliferation, invasion, and migration abilities were significantly suppressed in cells overexpressing SFRP1. The role of SFRP1 in NPC proliferation in vitro was consistent with Li and colleagues (19). Nude mice xenografts tumor model and lung colonization model were used to investigate the effects of SFRP1 in vivo and revealed that SFRP1 overexpression inhibited tumor aggressiveness of NPC.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…First, we examined the effects of SFRP1 on NPC cells using MTT, colony formation, wound-healing, and Transwell assays, which showed that cell proliferation, invasion, and migration abilities were significantly suppressed in cells overexpressing SFRP1. The role of SFRP1 in NPC proliferation in vitro was consistent with Li and colleagues (19). Nude mice xenografts tumor model and lung colonization model were used to investigate the effects of SFRP1 in vivo and revealed that SFRP1 overexpression inhibited tumor aggressiveness of NPC.…”
Section: Discussionsupporting
confidence: 75%
“…However, emerging evidence has indicated that SFRP1 may also be highly expressed in carcinomas and promote tumor proliferation or migration, such as in basal-like breast cancer (42), gastric cancer (43), and metastatic renal carcinoma (44). Recently, it has been reported that SFRP1 could suppress NPC cell proliferation in vitro (19). Notably, there is no research on SFRP1 in NPC metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to deletion, epigenetic modifications of DACT genes were also reported. For instance, DACT1 and DACT2 were reported to be methylated in hepatocellular carcinoma, oral squamous, gastric cancer, nasopharyngeal carcinoma, thyroid cancer, colon cancer and lung cancer (10,(26)(27)(28)(29)(30)(31). In addition, DACT3 was identified to have histone modifications in colorectal cancer (25,26,32).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we searched for methylated TSG candidates for digestive cancers through epigenomic (CpG methylome) study and expression profiling of a paired colon cancer cell line (HCT116 and HCT116-DKO with double knock-out of DNMT1 and DNMT3B 18, 19), and identified a candidate 16q24 TSG - Junctophilin-3 ( JPH3 ) as a methylated target. We systematically evaluated the inactivation of JPH3 by promoter CpG methylation in colorectal and gastric cancers, further explored its functions and mechanisms in the development of these cancers.…”
Section: Introductionmentioning
confidence: 99%